Analysis of Category I Cesarean Section Response Time on Maternal-Neonatal Outcomes at Adam Malik Hospital Medan - Mohammad Naufal; Sarma Nursani Lumbanraja; Iman Helmi Effendi; Edwin Martin Asroel; Hanudse Hartono; Sarah Dina (Medica Hospitalia : Journal of Clinical Medicine, 2025)
BACKGROUND: Maternal and neonatal mortality remain significant global health concerns. Category I cesarean sections are performed in life-threatening obstetric emergencies, with a recommended decision-to-incision interval (DII) of ≤30 minutes. AIMS: To evaluate the proportion of category I emergency cesarean sections performed < 30-minute response time at Adam Malik Hospital, Medan, and to identify factors contributing to delays. METHODS: This retrospective cohort study included 44 consecutively selected cases of category I emergency cesarean sections performed at Adam Malik Hospital, Medan, between January 1 and December 31, 2023. Eligible cases involved immediate threats to maternal or fetal life and had complete documentation of surgical timings. Time data including decision-to-incision interval and its components were extracted from electronic medical records and cross-validated with operating room and delivery ward logs. The primary outcome was decision-to-incision interval (DII), dichotomized at 30 minutes. Variables associated with DII (p <0.25) were included in multivariate analysis using Firth’s penalized logistic regression to account for small sample size and data separation. RESULTS: Only 43.2% of cases achieved a DII of ≤30 minutes. Multivariable analysis identified patient transfer time (AOR = 16.91, 95% CI: 2.19–358.36) and anesthesia duration (AOR = 27.21, 95% CI: 2.29–889.18) as significant predictors of delay. No significant associations were found between DII and adverse maternal or neonatal outcomes. CONCLUSION: Delays in patient transfer and anesthesia were the main contributors to prolonged DII in emergency cesarean sections. While these delays did not significantly impact short-term clinical outcomes, targeted improvements in emergency obstetric workflows may help hospitals meet national response time standards and enhance quality of care.